Socialisation into organised sports of young adolescents with a lower socio-economic status. Issue 3 (2nd April 2016) - Pot, Niek; Verbeek, Jan; van der Zwan, Joris; van Hilvoorde, Ivo
Abstract : Studies investigating sport socialisation often focussed on the barriers for youngsters from lower socio-economic status (SES) families to participate in sport. In the present study, the socialisation into sports of young adolescents from lower SES families that do participate in organised sports was investigated. A total of 9 girls and 12 boys from lower SES families (18 Dutch; three foreign ethnic background) from one city in the Netherlands who participated in organised sport were interviewed. Although multiple agents may be of influence on the socialisation process, this study was limited to the family, school and peers as potential socialising contexts. Drawing on the theoretical work of Bourdieu and Bernstein, parents were found to be the main influencers of the sports habitus of these young adolescents. The school context appeared to have no influence on their sport socialisation. Peers were found to have an influence on the choice for a specific type of sport. This interplay between socialising contexts for young adolescents from lower SES families is similar to the sport socialisation of youngsters from higher SES families. Therefore, it is suggested that if sport socialisation takes place, then the role of SES is less pronounced than often assumed. Moreover, there seem to be differences in the relative importance of the socialising contexts with younger children with a lower SES. Therefore, it is hypothesised that the relative importance of socialising agents changes over time. Although the findings may be limited to the specific sample of this study, they provide hypotheses that challenge the often-presumed importance of SES if sport socialisation takes place.